The apoptosis induced by silica nanoparticle through endoplasmic reticulum stress response in human pulmonary alveolar epithelial cells. (April 2019) - Wu, Tianshu; Zhang, Shihan; Liang, Xue; He, Keyu; Wei, Tingting; Wang, Yan; Zou, Lingyue; Zhang, Ting; Xue, Yuying; Tang, Meng
Abstract: Recently, the use of silica nanoparticles (SiO2 -NPs) and mesoporous silica nanoparticles (mSiO2 -NPs) in the biomedical field, such as biosensors, drug deliveries and bioactivator carriers, is increasing due to their special physiochemical properties. However, the biosafety assessment of them is far lagging behind their rapid application. In this study, we observed that both SiO2 -NPs and mSiO2 -NPs with certain exposed doses decreased the cell viability while increased the apoptosis rates in the human pulmonary alveolar epithelial cells (HPAEpiC). Generally, mSiO2 -NPs presented less toxic effects than SiO2 -NPs with same treated dose, which assures the positive application prospect of mSiO2 -NPs in the area of biomedicine. Since both SiO2 -NPs could be taken into cells and accumulated in the endoplasmic reticulum (ER), which resulted in pathologically morphological changes and subcellular organelle damages, we hypothesized that the ER stress response could be involved in the NPs-induced apoptosis. The findings suggested that SiO2 -NPs and mSiO2 -NPs exposure increased the expression levels of two ER stress markers, e.g. BiP and CHOP, which could be inhibited by the ER stress inhibitor 4-PBA, following with decreased apoptosis rates in HPAEpiC. Even though it is still unclear of the direct target of NPs causing ER stress response following with cell apoptosis, our findings provide a novel insight for researchers to explore the toxic mechanisms of SiO2 -NPs and mSiO2 -NPs in order to reduce the adverse effects of them. Highlights: SiO2 -NPs and mSiO2 -NPs both have value in the biomedical applications. SiO2 -NPs and mSiO2 -NPs exposure induced cell death and apoptosis. SiO2 -NPs and mSiO2 -NPs activated endoplasmic reticulum stress response to cause apoptosis. mSiO2 -NPs generally presented less toxicity than SiO2 -NPs.